Hybrid Particle-grid Modeling for Multi-scale Droplet/Spray Simulation - Yang, Lipeng; Li, Shuai; Hao, Aimin; Qin, Hong (Computer graphics forum, 2014)
This paper presents a novel hybrid particle‐grid method that tightly couples Lagrangian particle approach with Eulerian grid approach to simulate multi‐scale diffuse materials varying from disperse droplets to dissipating spray and their natural mixture and transition, originated from a violent (high‐speed) liquid stream. Despite the fact that Lagrangian particles are widely employed for representing individual droplets and Eulerian grid‐based method is ideal for volumetric spray modeling, using either one alone has encountered tremendous difficulties when effectively simulating droplet/spray mixture phenomena with high fidelity. To ameliorate, we propose a new hybrid model to tackle such challenges with many novel technical elements. At the geometric level, we employ the particle and density field to represent droplet and spray respectively, modeling their creation from liquid as well as their seamless transition. At the physical level, we introduce a drag force model to couple droplets and spray, and specifically, we employ Eulerian method to model the interaction among droplets and marry it with the widely‐used Lagrangian model. Moreover, we implement our entire hybrid model on CUDA to guarantee the interactive performance for high‐effective physics‐based graphics applications. The comprehensive experiments have shown that our hybrid approach takes advantages of both particle and grid methods, with convincing graphics effects for disperse droplets and spray simulation.